Efektivitas Kombinasi Ekstrak Lidah Buaya dan Lidah Mertua Terhadap Mortalitas Larva Aedes aegypti - Handayani Narendo Putri; Dita Pratiwi Kusuma Wardani; Isna Hikmawati; Muhammad Luthfi Almanfaluthi (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2022)
The Dengue Haemoragic Fever (DHF) vector control with synthetic larvicide has an impact on health and environmental problems, so alternative plant-based insecticides are needed. The study aims to determine the larvicidal effect of a combination with Aloe vera extract and Sansivieria trifasciata on the mortality of Aedes aegypti larvae. This study was conducted with experimental design by a post-test only with control groups design consisting of five groups. Two groups are positive control (1% temephos) and negative control (0% concentration). The other three groups served as a combination of Aloe vera extract and S. trifasciata Prain in ratio of 75%:25% (P1), 50%:50% (P2), and 25%:75% (P3). A total of 375 larvae were introduced in this study with three replications and with observation time of 30 minutes, 1 hour, 3 hours, 6 hours, 12 hours, 24 hours until totally died 100%. The mortality of Aedes aegypti larvae were analyzed by Kruskal Wallis and probit analysis to calculate LC50 and LC90. The larvae totally died 100% after 12 hours of exposure. There are significant differences in the mortality of Ae. aegypti larvae after administration of a combination with Aloe vera extract and S. trifasciata Prain. The P1 group (The combination with Aloe vera extract and S. trifasciata Prain with a ratio of 75%:25%) was the most effective in mortality of Ae. aegypti larvae. The LC50 value is 0.517% while the LC90 value is 2.121% within 6 hours. The combination group of Aloe vera extract and mother-in-law's tongue with a ratio of 75%:25% was the most effective in causing mortality of Ae. aegypti within 6 hours.